2010
DOI: 10.1007/s00128-010-0091-0
|View full text |Cite
|
Sign up to set email alerts
|

Residue and Bio-Efficacy Evaluation of Controlled Release Formulations of Metribuzin Against Weeds in Wheat

Abstract: Controlled release formulations of metribuzin in polyvinyl chloride, (emulsion); carboxy methyl cellulose, CMC and carboxy methyl cellulose- kaolinite composite, CMC-KAO are reported. The MET-CMC-KAO-3 (T(9)) formulation provided a superior control (76.1%) of weeds in field grown wheat in comparison to metribuzin 75 DF (57.14%) at the dose (350 g a.i. ha(-1)) after 90 days of sowing. The treatment (T(9)) reduced the dry weight of the weed flora after 30 days of sowing (4.0 g m(-2)) and significantly superior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Field trials of MET, which is effective against many broad-leaved weeds and herbs, confirmed its efficacy in traditional application against A. retroflexus and C. album in potato crops for pre-emergence tillage without a negative impact on the potato yield. 35 In the work of Tagour et al (2017), the effect of MET on the growth of different weeds that infest cereal crops was studied to show that the biomass of weeds remaining after treatment did not exceed 5–8%. 24 MET is an effective herbicide against various broadleaf weeds and grasses, and traditional pre-emergence soil applications of this herbicide in potato fields proved that it effectively controlled A. retroflexus and C. album without reducing the potato yield.…”
Section: Discussionmentioning
confidence: 99%
“…Field trials of MET, which is effective against many broad-leaved weeds and herbs, confirmed its efficacy in traditional application against A. retroflexus and C. album in potato crops for pre-emergence tillage without a negative impact on the potato yield. 35 In the work of Tagour et al (2017), the effect of MET on the growth of different weeds that infest cereal crops was studied to show that the biomass of weeds remaining after treatment did not exceed 5–8%. 24 MET is an effective herbicide against various broadleaf weeds and grasses, and traditional pre-emergence soil applications of this herbicide in potato fields proved that it effectively controlled A. retroflexus and C. album without reducing the potato yield.…”
Section: Discussionmentioning
confidence: 99%
“…12 Composite systems consisting of natural polymers (chitosan, carboxymethyl cellulose) and claylike compounds were used for loading different herbicides as the active ingredient. [29][30][31] Biodegradable polyesters of microbial origin, polyhydroxyalkanoates (PHAs), which are considered as promising polymer materials, have recently been studied for construction of agrochemicals with prolonged effects. The use of poly-3-hydroxybutyrate (P(3HB)) and 3-hydroxybutyrate-co-3-hydroxyvalerate copolymers (P(3HB-co-3 HV)) (the most common representatives of PHAs) for fabricating microspheres loaded with ametrine and atrazine herbicides was previously reported.…”
Section: Etcmentioning
confidence: 99%
“…Other authors describe composite systems based on clay and ethyl cellulose nanoparticles, wheat gluten, organic modified and unmodified clays, and a model pesticide ethofumesate, lignin with chloridazon and metribuzin . Composite systems consisting of natural polymers (chitosan, carboxymethyl cellulose) and claylike compounds were used for loading different herbicides as the active ingredient …”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that negligible metribuzin residue left in soil after wheat harvesting and this residue was within prescribed limit of EPA (Kumar et al 2010). The release of atrazine from polymeric matrix occurred by diffusion of AI through the matrix (Grillo et al 2012).…”
Section: +3mentioning
confidence: 85%